BRAF in metastatic colorectal cancer: the future starts now. (December 2015) - Orlandi, Armando
BRAF mutations are detectable in about 5–15% of metastatic colorectal cancer (mCRC) patients and represent a clear negative prognostic factor. While in BRAF-mutated (BRAFmt) metastatic melanoma TKI target therapies (BRAF and MEK inhibitor), both alone or in combination, have shown significant efficacy, in BRAFmt CRC single-agent BRAF-inhibitors as well as chemotherapy seem to be ineffective. The critical role of EGFR in CRC and its multiple downstreaming pathways seem to be involved in this lack of response. In recent years, preclinical investigations and retrospective studies slowly increased our knowledge on BRAFmt CRC. This review analyses preclinical data and discusses several clinical trials in order to explore new therapeutic strategies targeting BRAFmt mCRC.